Simplified traditional bubble-motion equation and air-gun wavelet simulation based on a Van der Waals gas model - Bing-Shou, He; Hao, Guo; Nan, Hu (Applied geophysics, 2021)
An air-gun source is the most commonly used excitation method in offshore seismic exploration. The excitation characteristics of an air-gun source affect seismic data quality. Far-field wavelet simulation is an important approach to study these characteristics. Compared to the measured wavelet, far-field wavelet simulation based on a traditional bubble-motion equation and ideal gas wavelet model has some disadvantages, such as a greater amplitude and smaller pulse attenuation velocity. Here, we start from the linear acoustic wave equation in the spherical coordinate system to deduce an improved, simpler bubble-motion equation and develop a Van der Waals gas wavelet model based on this equation. Unlike the existing methods, our method considers the high-pressure environment during actual excitation, heat exchange between the bubble and outside water, and change in the air flow at the muzzle. The results show that the far-field wavelet simulated using this model is closer to the measured wavelet than that of the ideal gas wavelet model. At the same time, our method has a more succinct equation and a higher calculation efficiency.